2023
DOI: 10.1039/d2na00782g
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium anchored Ti3C2Tx (MXene) nanosheets for electrocatalytic hydrogen production

Abstract: Atomically thin Ti3C2Tx (MXene) nanosheets with rich termination groups, acting as active sites for effective functionalization, are used as an efficient solid support to host rhenium (Re) nanoparticles for electrocatalytic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…37,41,131 In a work, ultrasmall Re nanoparticles (1-3 nm diameter) were anchored on Ti 3 C 2 T x (Mxene) nanosheets that displayed promising catalytic activity for HER. 132 HRTEM data proved introduction of Re in the lattice of Ti 3 C 2 T x due to the enlargement of lattice spacings of the latter. DFT data showed that the band structure of the composite to be metallic was due to the introduction of Re.…”
Section: Hermentioning
confidence: 85%
See 1 more Smart Citation
“…37,41,131 In a work, ultrasmall Re nanoparticles (1-3 nm diameter) were anchored on Ti 3 C 2 T x (Mxene) nanosheets that displayed promising catalytic activity for HER. 132 HRTEM data proved introduction of Re in the lattice of Ti 3 C 2 T x due to the enlargement of lattice spacings of the latter. DFT data showed that the band structure of the composite to be metallic was due to the introduction of Re.…”
Section: Hermentioning
confidence: 85%
“…Recently, Mxenes have drawn significant attention for electrochemical HER due to excellent electrical conductivity, abundant surface‐active sites, and chemical stability 37,41,131 . In a work, ultrasmall Re nanoparticles (1–3 nm diameter) were anchored on Ti 3 C 2 T x (Mxene) nanosheets that displayed promising catalytic activity for HER 132 . HRTEM data proved introduction of Re in the lattice of Ti 3 C 2 T x due to the enlargement of lattice spacings of the latter.…”
Section: Tmcs For Electrochemical Hermentioning
confidence: 99%
“…The HAADF-STEM and EDX elemental mapping images of the as-prepared Ti 3 C 2 T x sheets are shown in Figure S1, confirming the successful preparation of Ti 3 C 2 T x (MXene) with O, F, and Cl containing termination groups. These termination groups are often introduced on the surface of Ti 3 C 2 T x flakes during the etching process. , …”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 933.04 eV and 952.92 eV are assigned to the Cu 2p 3/2 and Cu 2p 1/2 peaks of the Cu 1+ state. 36 The core level spectrum of tellurium (Fig. 3(c)) exhibits a peak at binding energies 573.6 eV and 583.72 eV corresponding to the Te 3d 5/2 and Te 3d 3/2 of the Te 2À state.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Re has great potential to replace Pt, but more studies are needed in this regard. 18,19 Owing to its different valence states, rhenium oxide finds great potential in technological and industrial applications such as fuel cells, heterogeneous catalysis, etc 20,21 Reports suggest that ReO 3 exhibits localized surface plasmon resonance (LSPR) in the visible region similar to gold nanoparticles or metallic copper due to the available free electrons in the conduction band and the partially filled conduction band. 22 So far, very limited studies have been conducted on the HER properties of ReO 3 .…”
Section: Introductionmentioning
confidence: 99%